Groundwater management in an agro-industrial school in Argentina - Vuksinic, Evelyn (2019)
Introduction: water management is of paramount importance in productive activities, such as agriculture, livestock and industry, due to its direct impact on both the quality and the availability of this valuable resource. However, groundwater management is usually addressed under a non-integrated approach which originates a high risk of pollution as well as water shortage for food and animal production in the agro-industrial systems. Objective: to analyze water quality for human consumption, hydrogeological features, water demand, and discharge of liquid effluents on soil and surface water. Methods: we carried out a diagnostics of water management in an agro-industrial school located in Buenos Aires province, Argentina. The production system includes a bovine dairy farm; calf, pork and rabbit breeding; beekeeping; poultry farming; dairy and cheese factory; agriculture and fodder area; processing of meat, and orchard. To perform the analysis, we calculated water requirements for six productive activities and evaluated the hydrological features of the area through water table measurements considering the groundwater flow sense. We analyzed the groundwater quality seasonally during a period of a year through five water samples. We considered microbiological and physicochemical parameters and they were compared with recommended level by law, and we carried out the monitoring of residual chlorine during a week. Also, we evaluated the generation and disposal of effluents. Results: water was suitable for human consumption, although we detected variations in its quality indicators. We determined that the main issues hindering an integrated water management were the diversified production developed with high volumes of water demanded, the water quality deterioration by the agro-industrial productions carried out, and the hydrogeological features of the area. In addition, we measured a high water demand which is in conflict with groundwater shortage and the complex hydrological conditions of extraction in the studied area. Conclusion: this study demonstrated the usefulness of applying effective strategies to act on environmental-priority subjects and to develop good practices regarding water management from an integrated approach.